Impact of the Learning Environment on the Academic Performance of Business Administration Students - Guerrero, Lugo Manuel Barbosa; Rozo, Jairo Jamith Palacios (Journal of Ecohumanism, 2024)
A multiple linear regression model was developed with the aim of analyzing the impact of different dimensions of the learning environment on academic performance as perceived by university students. The sample consisted of 568 students from the Business Administration program at El Bosque University. The predictor variables included in the model were: learning strategies, technological challenges, effective technological platforms, and key competencies.The results showed that the model was statistically significant (F(4, 563) = 256.317, p < .001) and had high explanatory power, with a coefficient of determination of R² = 0.646, indicating that 64.6% of the variance in academic performance was explained by the learning environment variables. All predictor variables were statistically significant (p < .001).Among the factors analyzed, the effectiveness of technological platforms was the most influential predictor (β = 0.425), followed by learning strategies (β = 0.387), technological challenges (β = 0.380), and key competencies (β = 0.366). These results suggest that strengthening effective virtual environments, together with the development of digital skills and active learning strategies, contributes significantly to improving the perception of academic performance among university students.